Implementing Clil In Social Sciences class activities in English to foster the development of higher order thinking skills in 4th graders (2024)
Content Language Integrated Learning (CLIL) has been widely used as a teaching approach to teach language through content. Despite its diverse implementations to teach content knowledge and language simultaneously worldwide, little is known about the application of CLIL to foster higher-order thinking skills (HOTS). According to Anderson and Krathwohl (2001) in their revision of Bloom's taxonomy in 1956 this relationship remains unexplored, particularly in Social Sciences activities conducted in English in primary grades. This study aimed to explore the implementation of CLIL in Social Sciences activities in English in a Bilingual School to help 4th graders foster HOTS. Data was collected by applying a CLIL lesson plan mediated by Task-Based Learning (TBL) that consists of a macro-task, a set of micro-tasks, and a final task. This final activity consisted of creating an environmental magazine by the participants. The written discourse produced by each student was analyzed individually, drawing upon Taylor's approach to discourse analysis (2012) . Findings showed that the participants successfully developed HOTS during this study. The results revealed specific instances of student's cognitive skills development through their written work. The results obtained supported the effectiveness of the methodological decision made, such as drawing on Bloom's Taxonomy to establish learning objectives and measure the student's learning, and integrating CLIL with TBL. The strengths and weaknesses identified in students' cognitive skill development underscore the need to carefully consider task design and instructional strategies in future CLIL implementations. The findings of this research have the potential to inform other educators about the benefits and challenges of implementing CLIL to foster students' HOTS in Social Sciences activities in English.